Confronting the Combines: Producers' and Traders' Militancy in Western Nigeria (Nordic Journal of African Studies, 2000)
The Great Depression and the emergence of the Unilever Combine were the dominant events of Nigerian economic history during the 1930s (Ekundare 1973; Shenton 1986). A number of studies have examined these events and reactions to them but none has focussed on the militant action of Nigerian producers and traders ironically at a time that the worst effects of the Depression seemed to have abated (Hopkins 1966; Duffield 1969; Harneit-Sievers 1996). Though reference has been made to the cocoa 'pool' crisis of 1937/38 in several studies (Olorunfemi 1979; Harneit-Sievers 1996: 32-35) the episode has not been studied on its own merit or taken with similar ones to illustrate the theme of this essay. Of the latter, the effective, though sporadic, produce hold-ups by Urhobo oil palm producers in the Warri, Ondo and Ijebu Provinces of Western Nigeria, hitherto neglected in the literature, merits special attention especially given its links with the cocoa ‘pool’ crisis.